Financial literacy, social influence, goal clarity, and retirement experience / Wardatu Qistina Awang and Aida Abdullah - Awang, Wardatu Qistina; Abdullah, Aida (2021)
Retirement can be defined as the act of a person ending his/ her employment where the person needs to permanently stop his/ her work in the organization. Retirement is a life experience and a phase that all retirees face in their lifetime, after a long term of working or building careers. Most of the elderly choose to retire and enjoy their retirement lifestyle as a reward for themselves after they decide to end their career. However, the retirement experiences can be varied and differ from one person to another - the retirees would have either a leisure retirement experience or face many obstacles and negative retirement experiences. Thus, it is significant to evaluate the retirement experiences among the retirees as it is a must for all employed and self-employed persons arriving at the retirement age, and if one's contract of service is terminated. A good retirement experience can lead to a happy lifestyle among the retirees and improve mental and health conditions among the retirees. By leading better health, the retirees can improve their connection and relationship with others as well (Palmore, Fillenbaum & George, 1984; Rohwedder & Willis, 2010). Studies have examined that there are three main significant factors for retirement experiences; financial literacy, social influence, and goal clarity (Safari, Njoka & Munkawa, 2021; Hairodin, Ismail, Shamsuddin, & Miskam, 2021; Hill & Pfund, 2021). As such the aim of the study is to examine the relationship between the mentioned factors towards retirement experiences.